The effectiveness of including support people in a cognitive behavioural weight loss maintenance programme for obese adults: study rationale and design. Issue 2 (19th December 2013) - Rieger, E.; Treasure, J.; Swinbourne, J.; Adam, B.; Manns, C.; Caterson, I.
Summary What is already known about the subject Weight loss maintenance following participation in a behavioural weight loss programme remains a critical challenge in the obesity field. Social support predicts engagement in weight control behaviours, yet interventions designed to enhance social support have had only limited success in improving weight loss maintenance in obese adults. What this study adds The rationale for a novel approach to enhance the effectiveness of social support for weight loss maintenance is provided. Specifically, there is theoretical and empirical support for training support people in motivational interviewing in order to facilitate the development of self‐motivation for weight control in obese adults. Self‐motivation is, in turn, associated with long‐term behaviour change, including sustained engagement in weight control behaviours. The design and methodology of a study for evaluating the effectiveness of training support people in motivational interviewing to assist obese adults with weight loss maintenance is described. The well‐documented finding that obese adults have a high likelihood of weight regain following participation in behavioural weight loss programmes highlights the importance of developing more effective approaches for weight loss maintenance. One promising approach is to improve the quality of social support for effective weight control available to an obese individual by including support people in behavioural weight loss programmes. This paper describes the rationale and design of a randomized controlled trial that evaluates the effectiveness of training support people to assist obese adults in their weight management. The study entails a two‐arm randomized controlled trial in which obese participants take part in a 1‐year (26‐session) cognitive behaviour therapy group weight management programme, including motivational interviewing strategies (CBT‐MI). In one arm, participants receive CBT‐MI alone, while in the second arm (CBT‐MI‐SP), participants also have a support person who attends 10 group sessions designed to teach effective skills for supporting an individual in healthy weight control. More specifically, support people will be trained in skills that aim to promote self‐motivation for weight management. Assessments of anthropometric, medical, behavioural, motivational, psychological and social functioning take place at pre‐treatment, post‐treatment and a 1‐year follow‐up. By helping obese participants to increase and sustain their motivation and skills for weight control both during treatment and in the crucial period after treatment cessation through the ongoing input of support people, the CBT‐MI‐SP approach of the current study has the potential to effectively help patients to achieve sustained weight loss while minimizing the patient's need for ongoing, intensive weight control treatment with its attendant costs.